What are the determinants of older people adopting communicative e-health services: a meta-ethnography - Ayse Aslan; Freda Mold; Harm van Marwijk; Jo Armes (BMC, 2024)
Abstract Background Gradually, society has shifted more services online, with COVID-19 highlighting digital inequalities in access to services such as healthcare. Older adults can experience such digital inequalities, yet this group is also more likely to need medical appointments, compared to younger people. With the growing digitalisation of healthcare, it is increasingly important to understand how older people can best use communicative e-health services to interact with healthcare services. This is especially if older adults are to access, and actively interact with health professionals/clinicians due to their general health decline. This review aims to synthesise older adults' experiences and perceptions of communicative e-health services and, in turn, identify barriers and facilitators to using communicative e-health services. Methods A meta-ethnography was conducted to qualitatively synthesise literature on older adults' experiences of using communicative e-health services. A systematic search, with terms relating to 'older adults', 'e-health', 'technology', and 'communication', was conducted on six international databases between January 2014 and May 2022. The search yielded a total of 10 empirical studies for synthesis. Results The synthesis resulted in 10 themes that may impact older adults' perceptions and/or experiences of using communicative e-health services. These were: 1) health barriers, 2) support networks, 3) application interface/design, 4) digital literacy, 5) lack of awareness, 6) online security, 7) access to digital devices and the internet, 8) relationship with healthcare provider(s), 9) in-person preference and 10) convenience. These themes interlink with each other. Conclusion The findings suggest older adults' experiences and perceptions of communicative e-health services are generally negative, with many reporting various barriers to engaging with online services. However, many of these negative experiences are related to limited support networks and low digital literacy, along with complicated application interfaces. This supports previous literature identifying barriers and facilitators in which older adults experience general technology adoption and suggests a greater emphasis is needed on providing support networks to increase the adoption and usage of communicative e-health services.